Im Leben bleiben : Unterwegs zu Demenzfreundlichen Kommunen - Rothe, Verena; Gronemeyer, Reimer; Kreutzner, Gabriele (Gesellschaft der Unterschiede, 2015)
We are constantly growing older. At the same time, there are more and more people aging with dementia, who are merely being "taken care of". Clearly, we need alternatives to the established procedures. What can we do to create places where we can stay in life - rather than just staying alive? How can we turn the surroundings of people with and without dementia into "places of human warmth"? In Germany, numerous initiatives are on the rise: engaged people from politics, culture, churches, and youth work are creatively working towards dementia-friendly communities. The three authors, intimately familiar with the topic, show exploratory movements, obstacles, and first approaches.